Kecernaan Bahan Kering dan Bahan Organik dan Degradabilitas Serat pada Pakan yang Disuplementasi Tanin dan Saponin - Idha Muthiah Dwi Wahyuni; Anis Muktiani; Marry Christiyanto (Jurnal Agripet, 2014)
(Dry matter and organic matter digestibility and fiber degradability in feed by tannin and saponin supplementation)ABSTRACT. The study was conducted to assess the effect of the addition of tannins, saponin and their combinations on the feed, as defaunation agent in the dry matter and organic matter digestibility and ADF, NDF degradability. The study used an experimental method with a completely randomized design. The treatments were T0 : feed without supplementation; T1: feed supplementation with 1,2% saponin; T2 : feed with supplemetation combined of 0,5% tannin and 0,9% saponin; T3 : feed with supplementation combined of 1,0% tannin and 0,6% saponin; T4 : feed with supplementation combined of 1,5% tannin and 0,3% saponin and T5 : feed with supplementation with 2% tannins. The result showed that DMD and OMD increased with treatment added combination of tannin and saponin. The best result for DMD and OMD in combination of 1,5% tannin and 0,3% saponin. Degradability of ADF and NDF was decreased on the supplemented feed. The addition of a combination of tannins and saponins in the feed at dose of 1% tannin and 0.6% saponin showed the best result that increased of DMD and OMD and give good value on NDF and ADF degradability.